Formulation and evaluation of texture nutritional and sensory properties of plant-based cheese alternatives - Orawan Oupathumpanont; Suchanart Thippayajan; Natthakan Pannarat; Piangthan Chaisingkan; Sopida Wisansakkul (Applied Food Research)
This research studied the production processes and the physical, chemical, microbial, and sensory properties of appropriate formulas for plant-based cheese analogs products. The study investigated three factors: modified starch, categorized into three levels (8.00 %, 10.00 %, and 12.00 %); soy milk, classified into three levels (46.00 %, 49.00 %, and 52.00 %); and buttermilk flavor, differentiated into two levels (0.75 % and 1.00 %). A factorial design experiment resulted in 18 production formulas. The appropriate formula was selected based on chemical properties such as moisture, physical properties such as color, texture, meltability, and flowability with surface structural characteristics determined by scanning electron microscopy (SEM). The values obtained were grouped using hierarchical cluster analysis and the preferences of 60 consumers were tested using a 9-point hedonic scale. The plant-based cheese analogs were analyzed for nutritional properties, microorganisms, and consumer acceptance. The suitable formula for producing plant-base cheese analogs is formula number 4 with the following ingredients: casein protein powder, protein sludge from soy milk, soy milk, coconut oil, modified starch, carrageenan, xanthan gum, and buttermilk flavoring agent with percentages of 15.00, 15.00, 49.00, 11.00, 8.00, 0.70, 0.30. and 1.00, respectively. The nutritional value of 100 g. of plant-based cheese analogs product consisted of total energy 335.88 kilocalories, protein 11.42 g., fat 22.88 g., carbohydrates 21.07 g., dietary fiber 8.33 g., vitamin B2 0.193 mg., iron 0.93 mg., and calcium 104.82 mg. According to the Ministry of Public Health Announcement No 416 BE. 2021, microbiological quality is within the standard criteria for food pathogenic microorganisms. The overall liking score was moderate, suggesting that this product met the needs of lacto-vegetarian and plant-based consumers. This research results in plant-based products with taste, texture, and nutritional adequacy that are acceptable to consumers, and increase the choice of general consumers and lacto-vegetarian groups.